Prevalence and causes of blindness and low vision in southern Sudan. - Jeremiah Ngondi; Francis Ole-Sempele; Alice Onsarigo; Ibrahim Matende; Samson Baba; Mark Reacher; Fiona Matthews; Carol Brayne; Paul M Emerson (PLoS Medicine)
Background Blindness and low vision are thought to be common in southern Sudan. However, the magnitude and geographical distribution are largely unknown. We aimed to estimate the prevalence of blindness and low vision, identify the main causes of blindness and low vision, and estimate targets for blindness prevention programs in Mankien payam (district), southern Sudan. Methods and findings A cross-sectional survey of the population aged 5 y and above was conducted in May 2005 using a two-stage cluster random sampling with probability proportional to size. The Snellen E chart was used to test visual acuity, and participants also underwent basic eye examination. Vision status was defined using World Health Organization categories of visual impairment based on presenting visual acuity (VA). A total of 2,954 persons were enumerated and 2,499 (84.6%) examined. Prevalence of blindness (presenting VA of less than 3/60 in the better eye) was 4.1% (95% confidence interval [CI], 3.4-4.8); prevalence of low vision (presenting VA of at least 3/60 but less than 6/18 [corrected] in the better eye) was 7.7% (95% CI, 6.7-8.7); whereas prevalence of monocular visual impairment (presenting VA of at least 6/18 [corrected] in better eye and VA of less than 6/18 [corrected] in other eye) was 4.4% (95% CI, 3.6-5.3). The main causes of blindness were considered to be cataract (41.2%) and trachoma (35.3%), whereas low vision was mainly caused by trachoma (58.1%) and cataract (29.3%). It is estimated that in Mankien payam 1,154 persons aged 5 y and above (lower and upper bounds = 782-1,799) are blind, and 2,291 persons (lower and upper bounds = 1,820-2,898) have low vision. Conclusions Blindness is a serious public health problem in Mankien, and there is urgent need to implement comprehensive blindness prevention programs. Further surveys are essential to confirm these tragic findings and estimate prevalence of blindness and low vision in the entire region of southern Sudan in order to facilitate planning of VISION 2020 objectives.